Cu/CuxS‐Embedded N, S‐Doped Porous Carbon Derived in Situ from a MOF Designed for Efficient Catalysis. Issue 44 (8th June 2021) - Wang, Dongsheng; Fan, Mingyue; He, Tingyu; Zeng, Fanming; Hu, Xiaoli; Li, Chun; Su, Zhongmin
Abstract: The reasonable design of the precursor of a carbon‐based nanocatalyst is an important pathway to improve catalytic performance. In this study, a simple solvothermal method was used to synthesize [Cu(TPT)(2, 5‐tdc)] ⋅ 2H2 O (Cu‐MOF), which contains N and S atoms, in one step. Further in‐situ carbonization of the Cu‐MOF as the precursor was used to synthesize Cu/Cu x S‐embedded N, S‐doped porous carbon (Cu/Cu x S/NSC) composites. The catalytic activities of the prepared Cu/Cu x S/NSC were investigated through catalytic reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP). The results show that the designed Cu/Cu x S/NSC has exceptional catalytic activity and recycling stability, with a reaction rate constant of 0.0256 s −1, and the conversion rate still exceeds 90 % after 15 cycles. Meanwhile, the efficient catalytic reduction of dyes (CR, MO, MB and RhB) confirmed its versatility. Finally, the active sites of the Cu/Cu x S/NSC catalysts were analyzed, and a possible multicomponent synergistic catalytic mechanism was proposed. Abstract : Greater than the sum of its parts : Cu/Cu x S embedded N, S‐doped porous carbon (Cu/Cu x S/NSC) derived in situ from a designed Cu‐MOF was successfully synthesized. Porous Cu/Cu x S/NSC has a high catalytic reduction efficiency for 4‐NP ( k =0.0256 s −1 ) and dyes (CR, MO, MB and RhB) that is better than that of many copper‐based catalysts and even precious metal catalysts. The efficient catalytic reduction performance of Cu/Cu x S/NSC is inseparable from the synergistic catalysis of each component.